Abordagem para prospecção de cenários em instituto de pesquisa, desenvolvimento e inovação - Marcuzzo, Rafael (2018)
Through the realization of research, development and innovation projects, several technological advances in society were possible, provided by the generation and application of knowledge in systematized way. These projects are generally materialized in specialized institutions in the development of high-level scientific solutions aimed at increasing intellectual and material corporate, governmental or social power. Within organizations, in view of the current increasingly globalized competitiveness, the decision-making process is fundamental. In this perspective of search for continuous improvement, it is essential the vision of the future by managers and researchers as well as the industry, so that they work integrated and articulated. In addition, governments and companies have suffered from political and economic crises that, with the use of techniques such as structural analysis and strategic prospecting, would be possible to be premeditated and better managed. Therefore, this dissertation project proposes an approach to scenario exploration for the Institute for Smart Grids at Federal University of Santa Maria, which carries out research, development and innovation activities. This research is based on a bibliographical and documentary review on the characteristics of the sector, competitive intelligence and scenario exploration. This work listed a set of 54 variables of impact in the system studied, identified nine key variables to receive priority attention and the 10 groups of actors that command them. Through the identification of the objectives of these actors, a structure of power relations has been demonstrated that can be taken into account in the creation of present and future scenarios. This dissertation compiles several strategic aspects and how this information can be visualized to enhance the understanding of the research, development and innovation environment for the Institute for Smart Grids.